Developing visualisation prototypes from EZproxy server logs to understand information seeking behavior of Curtin Library users - Joseph, Pauline (2018)
During a 10-week, full-time research internship at Curtin University’s HIVE (Hub for Immersive Visualisation and eResearch) Center in Western Australia, Aaron Kent worked on visualising massive datasets documenting the information seeking behaviours of the university’s Robertson Library patrons at the request of Peter Green, Amanda Bellenger, and Matthew Robinson from the Curtin Library. Supervisor of the project, Senior Lecturer in Library, Records, Archives and Information Science, Dr. Pauline Joseph, talks to PDT&C about the research, curation of the datasets, and the emerging and valuable role of data visualisation.